The Prevalence of Urinary Tract Infection Following Flexible Ureterenoscopy and the Associated Risk Factors - Baseskioglu, Barbaros (Urology Journal, 2019)
Purpose: To evaluate the risk factors for urinary tract infection (UTI) after retrograde intrarenal surgery (RIRS). Materials and Methods: A retrospective evaluation of the records of patients who underwent RIRS from January 2013 to September 2016 was performed. All interventions were done by the same surgeon and by applying the same technique. Result: 111 patients were included in the study with a mean age of 47.5 years (range: 14-84 years). Postoperative infection rate was 12.6% (n= 14). SWL, preoperative double J stent insertion, localization, gender, and the operation side had no impact on origination of infectious complications (P > .05 for all). Preoperative infection history (P = .002, OR=7.96, %95CI: 2.0- 30.5), comorbidity score (P = .008, OR=7.79, CI%95: 1.7- 35.5), and residual fragments (P = .045, OR=5.12, CI%95: 1.03 – 25.36) were found to be the significant risk parameters of postoperative infectious complications. Conclusion: To reduce UTI complications, it is necessary to pay attention to patients with comorbidities, prescribe appropriate prophylactic antibiotic therapy for those who have urinary tract infection history and help patients to achieve stone free status.